Effect of CO2 Laser Irradiation on the Topographic and Optical Properties of CdO Thin Films - Sahar Naji Rashid et al. (مجلة بغداد للعلوم, 2020)
In this study, cadmium oxide (CdO) was deposited on glass bases by thermal chemical spraying technique at three concentrations (0.05, 0.1, 0.15) M and then was irradiated by CO2 laser with 10.6 μm wave length and 1W power. The results of the atomic force microscope AFM test showed that the surfaces of these CdO thin films were homogenous and that the laser irradiated effect resulted in decreasing the roughness of the surface as well as the heights of the granular peaks, indicating a greater uniformity and homogeneity of the surfaces. The optical properties were studied to determine laser effect. The results of optical tests of these thin films showed that the photoluminescence spectra and absorption shifted towards longer wavelengths with increased concentration, and the transmittance was high at high wave lengths. There was a decrease of energy gap values at (0.05, 0.15)M concentrations which were (2.1, 2.25)eV receptively, and an increase in the energy gap value at 0.1 M  concentration which was 2.55 eV, and other optical properties have been studied in this paper .In general, we observe that the values ​​of the optical constants of the concentrations (0.05, 0.15)M increase after laser irradiation and are lesser after irradiation at concentration 0.1 M.